PEMBERIAN ZINC DALAM TERAPI DIARE PADA ANAK - Pertiwi Febriana Chandrawati (Universitas Muhammadiyah Malang, 2010)
Abtract Diarrhea and nutrient deficiency in childhood period related to diminished vitamin and mineral in specific, micronutrients. This make children suffer from unbeneficial conditions. Zinc deficiencies disturbed the growth, increased the risk of diarrhea and respiratory tract infection. Zinc supplementation decrease symptoms of infection (diarrhea and cough) and increase development of child. Since 2004, WHO and UNICEF recommended zinc as supplementation in diarrhea. Zinc as diarrhea’s treatment based on Evidence that zinc has ability to protect gastrointestinal barrier and accelerate healing process. Zinc deficiencies were a big problem for children in development country. Zinc known at metallo-enzymes, polyribosomes, cell membrane, which influence cell growth and increase cell function. During diarrhea losses of zinc make body deficiency. WHO recommended zinc for diarrhea 10 mg/day for baby at 2-5 month, and 20 mg/days for 6 months child for 10 days. Keyword : Diarrhea – Zinc – micronutrient